BP1 motif in the human β-globin promoter affects β-globin expression during embryonic/fetal erythropoiesis in transgenic mice bearing the human β-globin gene - Zoueva, Olga P. (2008)
The binding of the transcription factor BP1 (β protein 1) to its site on the promoter of the adult β-globin gene has a silencing effect on β-globin transcription in vitro. To better understand the mechanism of BP1’s negative regulation of β-globin expression, we developed transgenic mice bearing a human β-globin locus-containing cosmid. Specifically, we introduced a mutated BP1 binding site (mtBP1) into the promoter of the β-globin gene sequence of this cosmid construct. In the mtBP1 mice, we detected a more than 20-fold increase in human β-globin expression in the yolk sac-derived blood at E10.5, a 3-fold increase in fetal livers at E13.5, and an approximately 1.4-fold increase in adult reticulocytes compared with control mice bearing the human β-globin gene with the wild-type BP1 binding site sequence (wtBP1). Our in vivo observations support the contention that the BP1 binding site of the β-globin promoter plays an important role in the regulation of transcription of the adult β-globin gene.